Analysis of government policies impact on cotton and wheat production in Gezira Scheme (seasons 2003-2007) - Elnagarab, Elsayed; Alhag, Mohamed; Alamin, Abbas (Gezira Journal of Agricultural Science; Vol 8 No 1 (2010), 2010)
The main objective of this paper was to analyze the impact of the Sudanese government agricultural policies on cotton and wheat production in the Gezira Scheme in the seasons 2003-2007 in terms of efficiency, competitiveness and comparative advantages. The study depended on data and information collected from different sources. The policy analysis matrix (PAM) was adopted as an analytical model to achieve the above objective. Nominal protection coefficient of outputs, nominal protection coefficient of inputs, effective protection coefficient, profitability coefficie-nt, domestic resources coefficient and international value added were calculated for the seasons under consideration and compared with those obtained by Adam (1996). The results showed that the government policies discouraged Gezira tenants to produce cotton and its outputs had been subjected to taxes throughout all seasons under consideration, where on the other hand, the government policies provided incentives and favored production of wheat in the Gezira Scheme. Consequently it could be concluded that, although the overall  impact  of the government polices was tending to be worse regarding the protection and competitiveness, but still there were comparative advantages in cotton and wheat production. For providing more incentives for food and cash crops, the study recommended that the Sudanese government should provide subsidies for cotton producers in addition to the rehabilitation of the Gezira Scheme infrastructure. إن الهدف الأساسي لهذه الدراسة هو تحليل تأثير السياسات الزراعية التي اتبعتها الحكومة السودانية على إنتاج القطن والقمح في مشروع الجزيرة خلال المواسم 2003-2007 فيما يختص بالحماية والتنافسية والميزة النسبية. اعتمدت الدراسة على البيانات والمعلومات الثانوية التي تم جمعها من مصادرها  الأولية والثانوية التقليدية والالكترونية. تم استخدام مصفوفة تحليل السياسة وهى إحدى أدوات التحليل الكمي لتحقيق هدف الدراسة حيث حسبت أهم مؤشرات تحليل السياسة وهى معامل الحماية الاسمية للمنتجات، معامل الحماية الاسمية للمخرجات، معامل الحماية الفعال، معامل حماية الموارد المحلية، القيمة المضافة، ومعامل الربحية ثم قورنت نتائج الدراسة مع ما توصلت إليه دراسة ادم (1996). خلصت الدراسة إلي أن السياسات الحكومية لا تشجع  مزارعي مشروع الجزيرة على إنتاج  القطن وان مخرجاته ظلت تعانى من فرض الضرائب طوال مواسم الدراسة بينما  تقدم تلك السياسات مجموعة من الحوافز التي تشجع على إنتاج محصول القمح بالمشروع كما أن مدخلات المحصولين مازالت تعانى من فرض ضرائب باهظة ولكن رغم ذلك ما زالت هنالك ميزة نسبية لإنتاج القطن والقمح في مشروع الجزيرة.